A novel reconfigurable PD based on complementary hybrid circuit. Issue 2 (17th February 2021) - Lei, Peng; Yang, Hong; Zhao, Shiwei; Peng, Hong; Zhang, Hongsheng
ABSTRACT: Reconfigurable methods including areflective phase-shifter circuit are proposed based on complementary hybrid network power divider (PD). The analysis shows that this method can achieve continuously tunable power division ratio (PDR) and wide phase difference by changing the two horizontal transmission lines of the complementary hybrid network. In this way, areconfigurable PD based on acomplementary hybrid circuit-based reflective phase-shifter is designed to work at 2.45 GHz by replacing two horizontal transmission lines with 50 Ω reflective phase-shift circuits. The PDR of this fabricated reconfigurable PD is changed to the range of −29.12 to −0.24 dB, with the bias voltage being 0–8 V; meanwhile, the return loss and isolation are better than 23.2 dB.